2022
DOI: 10.1515/bmt-2022-0054
|View full text |Cite
|
Sign up to set email alerts
|

Effect of non-return valves on the time-of-arrival of new medication in a patient after syringe exchange in an infusion set-up

Abstract: The presence of a non-return valve in an infusion set-up is expected to affect the time-of-arrival of new medication in a patient after syringe exchange. Using Computational Fluid Dynamics (CFD) we have studied the flow through a typical non-return valve, focusing on two separate effects: (A) the overall delay in the time-of-arrival, and (B) timing effects due to the distortion of the Poiseuille flow profile in the non-return valve. The results show that (A) the additional delay in time-of-arrival of new medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…short-acting critical drugs. 10,14,19,20 Microinfusions are run continuously and fresh infusions are required on a regular basis. Recent clinical research has demonstrated that, independent of the changeover strategy used, at least 25% of critical haemodynamic events occurred around changeover when administering norepinephrine to critically ill adult patients.…”
Section: Clinical Tip 10: Minimise Pump Start-up Delays and Flow Irre...mentioning
confidence: 99%
See 1 more Smart Citation
“…short-acting critical drugs. 10,14,19,20 Microinfusions are run continuously and fresh infusions are required on a regular basis. Recent clinical research has demonstrated that, independent of the changeover strategy used, at least 25% of critical haemodynamic events occurred around changeover when administering norepinephrine to critically ill adult patients.…”
Section: Clinical Tip 10: Minimise Pump Start-up Delays and Flow Irre...mentioning
confidence: 99%
“…This is especially relevant during syringe changeover when infusing highly concentrated, i.v. short-acting critical drugs 10,14,19,20 …”
Section: Clinical Tip 10: Minimise Pump Start-up Delays and Flow Irre...mentioning
confidence: 99%